AAA identity management security: the complete, authoritative guide to implementing, configuring, and managing AAA with CiscoSecure ACS - Santuka, Vivek; Banga, Premdeep; Carroll, Brandon (Indianapolis, IN : Cisco Press, 2011)
The book covers all aspects of implementing, administering, and troubleshooting Cisco AAA solutions on Cisco routers, switches, access points, firewalls, and concentrators.
Includes index.
uaj 2/12/2013
Loans
Keywords: Computer networks -- Security measures; Computers -- Access control; Identification; Authentication